"Recommendations of the World Congress of Experts on Joint Endoprosthetics" - Staff of "Orthopaedics, Traumatology; Prosthetics" (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
In early 2025, the manual "Recommendations of the World Congress of Experts on Joint Endoprosthetics" was published, recommended by the Scientific and Publishing Council of the National Academy of Medical Sciences of Ukraine and designed for a wide range of users.